Volume 14: Emerging Technologies; Safety Engineering and Risk Analysis; Materials: Genetics to Structures 2015
DOI: 10.1115/imece2015-53258
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Corrosion Behaviour of Aluminium Alloy 2014 T-651 Friction Stir Welds Using Stress Corrosion Cracking

Abstract: Stress Corrosion Cracking (SCC) is the initiation and slow growth of cracks under the influence of tensile stresses and aggressive corrosion environment. Al alloy 2014 T 651 was solution heat treated and stress-relieved. In the present work, Stress Corrosion Cracking (SCC) experimental arrangement has been used to test the severity of aluminium alloys under particular environmental conditions. Sound welds were obtained with Friction Stir Welding at rotational speed of 800 rpm and welding speed of 200 mm/min. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For FSWed joints of Al alloy 2014-T651 Kollapuri [379] reported that HAZ comprised large grain size compared to the nugget zone.…”
Section: Microstructure Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…For FSWed joints of Al alloy 2014-T651 Kollapuri [379] reported that HAZ comprised large grain size compared to the nugget zone.…”
Section: Microstructure Evolutionmentioning
confidence: 99%
“…Studying stress corrosion cracking SCC of FSWed joints of 2014-T651 alloy, Kollapuri [379] reported that at 70 % yield, stress induced was lower and so the material failure was determined by its hardness.…”
Section: Mechanical Properties Hardnessmentioning
confidence: 99%
“…For the FSW joints of the 2014-T651 alloy, Kollapuri [499] reported that the HAZ comprised a larger grain size than the NZ.…”
Section: Microstructure Evolutionmentioning
confidence: 99%
“…Studying the stress corrosion cracking (SCC) of FSW joints of the 2014-T651 alloy, Kollapuri [499] reported that, at 70% yield, the induced stress was lower, so the material failure was determined by its hardness.…”
Section: Hardnessmentioning
confidence: 99%
“…Aluminum Alloys are widely used in engineering structures, because they are of lightweight and better corrosion resistance [1]. e most common alloying elements for Aluminum Alloys is Copper (Cu), Magnesium (Mg), Manganese (Mn), Silicon (Si), Tin (Sn), and Zinc (Zn).…”
Section: Introductionmentioning
confidence: 99%